2011
DOI: 10.1029/2011gl048738
|View full text |Cite
|
Sign up to set email alerts
|

New global observations of the terrestrial carbon cycle from GOSAT: Patterns of plant fluorescence with gross primary productivity

Abstract: [1] Our ability to close the Earth's carbon budget and predict feedbacks in a warming climate depends critically on knowing where, when and how carbon dioxide is exchanged between the land and atmosphere. Terrestrial gross primary production (GPP) constitutes the largest flux component in the global carbon budget, however significant uncertainties remain in GPP estimates and its seasonality. Empirically, we show that global spaceborne observations of solar induced chlorophyll fluorescence -occurring during pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
899
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 881 publications
(927 citation statements)
references
References 34 publications
24
899
2
2
Order By: Relevance
“…With high-spectral resolution spectrometers that can resolve atmospheric absorption bands (Fraunhofer lines), fluorescence can now be passively detected from a distance as a small signal present in the "gaps" of the solar spectrum [27]). This solar-induced fluorescence (SIF) is closely linked to gross primary productivity (GPP) [28][29][30], however, the coarse spatial and temporal scales of many satellite-based SIF measurements cannot resolve detailed seasonal dynamics or explain underlying mechanisms driving changes in GPP. At leaf-scales, the PAM method can measure steady-state chlorophyll fluorescence (F S ) without delivering a saturating pulse of light, which is an analogous measurement to SIF measured at large scales, as both can be measured under ambient illumination, allowing for more mechanistic studies of individual leaves and canopies.…”
Section: Introductionmentioning
confidence: 99%
“…With high-spectral resolution spectrometers that can resolve atmospheric absorption bands (Fraunhofer lines), fluorescence can now be passively detected from a distance as a small signal present in the "gaps" of the solar spectrum [27]). This solar-induced fluorescence (SIF) is closely linked to gross primary productivity (GPP) [28][29][30], however, the coarse spatial and temporal scales of many satellite-based SIF measurements cannot resolve detailed seasonal dynamics or explain underlying mechanisms driving changes in GPP. At leaf-scales, the PAM method can measure steady-state chlorophyll fluorescence (F S ) without delivering a saturating pulse of light, which is an analogous measurement to SIF measured at large scales, as both can be measured under ambient illumination, allowing for more mechanistic studies of individual leaves and canopies.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that space-borne suninduced chlorophyll fluorescence (SIF) observations offer new possibilities for monitoring photosynthesis from space (Frankenberg et al 2011. Chlorophyll fluorescence is an electromagnetic emission in the 650-800 nm range originating at the core of photosynthetic machinery.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19]. The first global maps of SIF were derived using data from the Greenhouse Gases Observing Satellite (GOSAT) (20)(21)(22)(23). Despite the complicated photosynthesis-SIF relationships and the convolution of the signal with canopy structure (16), SIF retrievals showed high correlations with data-driven GPP estimates at global and annual scales (21,22), as well as intriguing patterns of seasonal drought response in Amazonia (24,25).…”
mentioning
confidence: 99%
“…The first global maps of SIF were derived using data from the Greenhouse Gases Observing Satellite (GOSAT) (20)(21)(22)(23). Despite the complicated photosynthesis-SIF relationships and the convolution of the signal with canopy structure (16), SIF retrievals showed high correlations with data-driven GPP estimates at global and annual scales (21,22), as well as intriguing patterns of seasonal drought response in Amazonia (24,25). Recently, a global SIF data set with better spatial and temporal sampling than that from GOSAT was produced using spectra from the Global Ozone Monitoring Experiment-2 (GOME-2) instrument onboard the MetOp-A platform (26) (see SI Appendix, SIF Retrievals).…”
mentioning
confidence: 99%